Filsafat Pendidikan Islam: Kajian Pemikiran Ibnu Khaldun - Zulfa Azka Azkia; Nurul Zhafirah Muslim (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
During the glory of Islamic Civilization we encountered many influential Islamic figures who were able to master knowledge in various fields and branches of science. Many discussions werw studied by these figures. According to him, this allows us to examine the things that form the struggle of the ilama to essure that islamic value are always maintained and can entar into people’s lives, especially their application in the realm of education, this is often a factor in the development and decline of Islam in that era. Examining the understanding of knowledge from the these figures can open up insight inti the study of Islamic education that spread during the glorious era of Islam. One of them is about an Islamic sociological philosopher whose work is considered very fascinating. This research is qualitative research using research using literature review (Library Research). The source of data collection is related book literature and journal. In this research, the aouthor examines the realm of educational development according to Ibnu Khaldun. He was the one who succeeded in reviving intelectual thought in Islam in the Middle Ages.